A new species and a new combination of Chloridium from southwest China - Wei, Tian-Peng; Wang, Kun-Ying; Zhang, Hong; Luo, Ming-Yan; Jia, Wei-Yu; Zeng, Yan; Jiang, Yu-Lan (Phytotaxa, 2022)
A new species, Chloridium paucisetosum, was isolated from soil in Guizhou Province, China. The species is distinguished from other Chloridium species by its cylindrical or lageniform conidiogenous cells producing obovoid or ellipsoidal conidia without mucoid appendages, and apical branched conidiophores. Phylogenetic analysis based on combined ITS and LSU sequence data showed that C. paucisetosum formed a monophyletic clade and clearly separated from other Chloridium species. It is compared with other similar species and their phylogenetic relationships are discussed. Morphology and phylogenetic analyses support the introduction of the new species C. paucisetosum. In addition, a previously described species Phialocephala humicola is synonymized under the genus Chloridium.